2015
DOI: 10.1021/acs.nanolett.5b03068
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale and Single-Dot Patterning of Colloidal Quantum Dots

Abstract: Using an optimized lift-off process we develop a technique for both nanoscale and single-dot patterning of colloidal quantum dot films, demonstrating feature sizes down to ∼30 nm for uniform films and a yield of 40% for single-dot positioning, which is in good agreement with a newly developed theoretical model. While first of all presenting a unique tool for studying physics of single quantum dots, the process also provides a pathway toward practical quantum dotbased optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 35 publications
0
76
0
Order By: Relevance
“…Additionally, the ability to dynamically regulate the coupling in single‐molecule heterostructures represents a powerful tool toward the fabrication of stimuli‐responsive and reconfigurable systems for both optoelectronic and sensing applications. Lastly, a solution‐based approach,3 in contrast to top‐down lithographic methodologies,4 is highly desirable toward the facile and low‐cost (solution processable) fabrication of nanoscale devices. [[qv: 1b,5]]…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ability to dynamically regulate the coupling in single‐molecule heterostructures represents a powerful tool toward the fabrication of stimuli‐responsive and reconfigurable systems for both optoelectronic and sensing applications. Lastly, a solution‐based approach,3 in contrast to top‐down lithographic methodologies,4 is highly desirable toward the facile and low‐cost (solution processable) fabrication of nanoscale devices. [[qv: 1b,5]]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover in [19] we showed that a dipole emitter embedded in a SiN waveguide with optimized dimensions can couple up to 43% of its emission to a single waveguide mode, with a 95% polarization ratio. Finally, we experimentally demonstrated the capability for positioning individual quantum dots at a predefined location with high yield [20]. The combination of these results shows the hybrid QD-SiN platform offers the potential for realizing efficient on chip single photon sources in combination with complex photonic circuits.…”
Section: Introductionmentioning
confidence: 78%
“…Work by Xie et al. has shown a versatile and straightforward technique of positioning a single QD on a chip by using lithography and lift‐off processes. The technique can register a single QD in a desired location with a yield of up to 40% and thus provides an efficient tool for the development of on‐chip devices based on a single QD.…”
Section: Colloidal Qd‐based Light Emittersmentioning
confidence: 99%